A marca Imperator: memória, cultura e experiência - Rosa, Vera Zunino (2017)
This research focus on the study of the brand Imperator Centro Cultural João Nogueira, as a visual identity, and its symbolic value, which reaches issues of memory and experience. What the brand represents and how its image is perceived and built by its customers. The representation linked to the history of the place, and its importance to the region. The Imperator cinema, is a source of pride for Méier district residents in Rio de Janeiro, which pushed the city towards the north and facilited its modernization, serves as a basis for understanding the importance that the brand generates and its reflection in the memory of the neighborhood. The affective memory, linked to the brand and the construction of new meanings based on the present of the cultural equipment, are part of this study and of the interviews done in the site. Semiotics is the science that permeates the various authors and makes it possible to invoke the components that shape the meaning of the brand from its qualitative aspects and to analyze the associations that transcend the sense of visuality and delineate its symbolic potential. The perception of these values can be used in branding action strategies